Analysis of the Influence of Project Communication Management on Owner Decision to Improve Implementation Time Performance in High-Rise Building Construction Projects - Muhaemin, Aris; Suroso, Agus (ASTONJADRO, 2025)
Building high-rises is one example of a property business sector construction project involving various interested parties. The issue that high-rise building construction projects frequently encounter at PT X as the property developer prevented the intended completion date from being met. In high-rise building construction projects, this study examines how owner decisions affect implementation time performance based on project communication management. This study used multiple regression analysis with SPSS and SemPLS, and the sample size consisted of 80 respondents. According to the research findings, project communication management positively and significantly influences owner decisions in high-rise building construction projects; owner decisions also positively and significantly influence contractor performance in high-rise building construction projects; and owner decisions positively and significantly influence consultant performance in building construction projects. Owner decisions about high-rise structures have a favorable and significant impact on supplier performance in high-rise building construction projects and supplier, contractor, and consultant performance. has a favorable and noteworthy impact on high-rise building construction projects’ schedule performance.